2020
DOI: 10.1038/s41598-020-68910-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardanol derived P, Si and N based precursors to develop flame retardant phenolic foam

Abstract: A novel eco-friendly halogen-free cardanol-based flame retardant with P, Si, and N on the chain backbone (PSNCFR) was synthesized and incorporated into phenolic foams (PFs). PSNCFR was comprehensively investigated via Fourier transform infrared spectroscopy and nuclear magnetic resonance. PSNCFR endowed PFs with flame retardancy, contributed to generating a composite char defense against flames, and efficiently prevented smoking from PFs. PSNCFR introduction improved the flexural strength of the PFs to approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The C 1s spectrum peaks are centered at 284.5, 286.6, and 288.7 eV, which could be assigned to C–C and C–H of the aliphatic and aromatic species, C–O group, and C=O group, respectively. 52 In Figure S6 (K1 HGM syntactic foam char), one C 1s peak has been observed at 282.5 eV, which may be attributed to the Si–C group. 52 , 60 The O 1s spectrum shows two peaks at 531.1 and 532.5 eV, in which the first one may be related to the P=O or C=O groups and the second one may be assigned to C–O–C groups, respectively.…”
Section: Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The C 1s spectrum peaks are centered at 284.5, 286.6, and 288.7 eV, which could be assigned to C–C and C–H of the aliphatic and aromatic species, C–O group, and C=O group, respectively. 52 In Figure S6 (K1 HGM syntactic foam char), one C 1s peak has been observed at 282.5 eV, which may be attributed to the Si–C group. 52 , 60 The O 1s spectrum shows two peaks at 531.1 and 532.5 eV, in which the first one may be related to the P=O or C=O groups and the second one may be assigned to C–O–C groups, respectively.…”
Section: Results and Discussionmentioning
confidence: 96%
“… 52 In Figure S6 (K1 HGM syntactic foam char), one C 1s peak has been observed at 282.5 eV, which may be attributed to the Si–C group. 52 , 60 The O 1s spectrum shows two peaks at 531.1 and 532.5 eV, in which the first one may be related to the P=O or C=O groups and the second one may be assigned to C–O–C groups, respectively. 52 In the case of K1 foam char, only one peak at 531.7 eV has been noticed.…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the modification provides high smoke inhibition. Total smoke production (TSP) calculated from the cone calorimetry studies showed a 64.5 % decrease [149].…”
Section: Cardanol-substituted Phenolic Foammentioning
confidence: 99%